Analysis of Pulmonary Function Test among Grind-stone Workers in Srakaew Province, 2003-2017 - Pattamak, Chadaryoot (Journal of Health Science of Thailand, 2017)
The aims of this study were to describe the rate of pulmonary changing among these workers. This study was a descriptive study among grind-stone workers at Srakrew province, on the second week for February each year from 2003 to 2017. The study began in October 2003 and ended in Febuary 2017 in one enterprise. This year there were 10 workers still being in this study. Study methods included literature review, collecting of relevant information and analysis by statistical package program. Regression was the main statistical method to describe this study. The data of the co-efficient statistics trend among 15 years showed in forced expiratory volume in one second (FEV1), forced vital capacity (FVC) and percentage of FEV1, FVC equal to -0.027, -0.003 and -0.008 .The trend of priority setting by job working were maintenance equal to -0.01327, messenger driving equal to -0.01296, truck driving equal to -0.01163, collecting dust equal to -0.01004 and grind-stone mill -0.00559. The co-efficient statistics trend for male was -0.00974 and for female was -0.01004.